Difficulty in Assessing and Diagnosing Autistic Children in Psychological Educational Centers for Mentally Retarded Children from the Point of View of the Psychological Educational Team -Exemple Bejaia State - - بشاطة, منير (Milev Journal of Research and Studies, 2023)
The current study aimed to identify the difficulty in evaluation and diagnosis of autistic children at the level of the psychological-educational focus, according to the point of view of the psychological-educational team working in these centers. Mentally in Algeria, Studious results reached to aaaan there difficulties on level the mental relationship between the team educational and custodians custodians of children of the loneliness., in in addition to difficulties administrative and financial on level the mental centers aalbydaaGwjyt for the backward mental evaluation and the diagnosis hinders the diagnosis, and as your lowness the diagnosis for faction weakened on level acquisition of the occupational qualifications the corollary for the evaluation and the diagnosis the loneliness.